Analytical Challenge in Postmortem Toxicology Applied to a Human Body Found into a Lake after Three Years Immersion. Issue 5 (10th August 2015) - Morini, Luca; Vignali, Claudia; Tricomi, Paolo; Groppi, Angelo
Abstract The body of a 30‐year‐old woman was found in Como lake at a depth of about 120 meters in her own car after 3 years of immersion. The aim of this study was to evaluate psychoactive drugs as well as alcohol biomarkers in biological matrices. The following analyses were initially performed: GC‐MS systematic toxicological analysis on biological fluids and tissues; GC‐MS analysis of drugs of abuse on pubic hair; direct ethanol metabolite determination in pubic hair by LC‐MS/MS. After 7 years, the samples, that had been stored at −20°C, were re‐analyzed and submitted to an LC‐MS/MS targeted screening method, using multiple reaction monitoring mode. These analyses detected citalopram (150–3000 ng/mL), desmethylcitalopram (50–2300 ng/mL), clotiapine (20–65 ng/mL), and ethyl glucuronide (97 pg/mg). The methods showed an acceptable reproducibility, and the concentrations of citalopram and desmethylcitalopram calculated through the two analytical techniques did not significantly differ in biological fluids.